(untitled) (International Journal of Interreligious and Intercultural Studies, 2024)
The existence of tourism in Pedawa Village, Banjar District, Buleleng Regency is inseparable from the tradition of making iconic palm sugar. Advances in science and technology have challenged the existence of this tradition in the process of passing it on to the younger generation. Therefore, the existence of this tradition is still being maintained, both to maintain the traditional order and the sustainability of community-based tourism. Efforts to revitalize the tradition of making palm sugar in Pedawa Village involve two dimensions, namely the “sekala” (real) dimension and the “niskala” (abstract) dimension. The sekala dimension is carried out through concrete actions, namely sugar palm conservation and product innovation, while the noetic dimension is carried out through sacredization based on Hindu teachings combined with local wisdom. The study conducted in Pedawa Village is quite interesting because the revitalization carried out can be an example amidst the negative issues of the tourism sector which are synonymous with resource exploitation, degradation of traditional values, and desacralization. Through the results of this research, it is hoped that it can create a strong tradition and impact on tourism that can be managed in a sustainable manner. Keywords: revitalization, sekala, niskala, palm sugar, sustainable tourism.